Risk Analysis and Mitigation in the Coffee Supply Chain (Case Study: XYZ MSME, Klungkung) - Manik, Roulina; I Wayan Gede Sedana Yoga; Ni Putu Suwariani (Cita konsultindo, 2025)
XYZ is one of the coffee processing MSMEs located in Klungkung Regency, Bali. In carrying out its operations, this MSME encounters several problems, one of which is the lack of green bean raw materials. This condition has the potential to cause production targets to not be achieved, so that consumer demand cannot be met. This problem can cause losses for MSME, so efforts are needed to anticipate and reduce the risks that occur due to the lack of raw materials. This study aims to identify risk events and risk sources, as well as to design mitigation strategies to minimize the impact of risks on the supply chain at XYZ MSME. The HOR method consists of two phases. Identifying risk events and sources is done in HOR phase 1, and designing mitigation solutions for priority risk agents is done in HOR phase 2. According to the study's findings, there are 56 risk agents and 31 risk events, with 23 risk agents prioritized according to their Aggregate Risk Potential (ARP) value. Furthermore, 17 mitigation strategies were designed to reduce risk, and nine of these strategies were selected as the top priorities in risk management. These priority strategies include setting quality standards for green bean suppliers, implementing a strict penalty or price discount system, providing a buffer stock of raw materials, implementing a safety stock system for raw materials, adding potential suppliers from different locations, improving supplier selection and evaluation, establishing cooperation contracts for a specific period of time, with setting price standards, preparing new suppliers, and forming a Quality Control (QC) team.